2007
DOI: 10.1200/jco.2007.12.0329
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Effusion in Patients With Chronic Myelogenous Leukemia Treated With Dasatinib After Imatinib Failure

Abstract: Pleural effusions occur during dasatinib therapy, particularly among patients in AP or BP. A twice-daily schedule may result in a higher incidence of pleural effusion. Close monitoring and timely intervention may allow patients to continue therapy and achieve the desired clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
349
6
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(383 citation statements)
references
References 31 publications
15
349
6
13
Order By: Relevance
“…17 Interestingly, recent studies have suggested that dasatinib induced pleural effusions may be immune mediated. [18][19][20] These observations are concordant with our results, as almost all our patients with LGL proliferation had pleural effusions or pneumonitis. Analysis of lymphocytes from pleural fluid showed a similar phenotype (CD3 þ CD8 þ CD57 þ ) and genotype (identical T-cell clone) as simultaneously observed in peripheral blood.…”
Section: Discussionsupporting
confidence: 92%
“…17 Interestingly, recent studies have suggested that dasatinib induced pleural effusions may be immune mediated. [18][19][20] These observations are concordant with our results, as almost all our patients with LGL proliferation had pleural effusions or pneumonitis. Analysis of lymphocytes from pleural fluid showed a similar phenotype (CD3 þ CD8 þ CD57 þ ) and genotype (identical T-cell clone) as simultaneously observed in peripheral blood.…”
Section: Discussionsupporting
confidence: 92%
“…28,32 The use of high concentrations raises the concern of drug toxicity, as pleural effusion is a welldocumented side effect of dasatinib. 33 In the current study, we define sensitivity as IC 50 less than 128 nM. Using this criterion, five cell lines including LY1, LY7, LY8, LY10 and VAL are considered sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Most recently, an increase in the right ventricular systolic pressure, a non invasive surrogate marker of PAP, was detected at the onset of PE in a subset of CML patients treated with dasatinib, suggesting the possibility of drugrelated PAH and subsequent subclinical heart failure. 3 Notably, the left ventricular ejection fraction remained unchanged in all patients at the time of PE. Discontinuation of dasatinib resulted in resolution of PE and a significant decrease in the right ventricular systolic pressure.…”
mentioning
confidence: 87%